2014
DOI: 10.1259/bjr.20140377
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dose escalation on TCP, recurrence and second cancer risks: a mathematical study

Abstract: VSK Manem and A Dhawan contributed equally to this article.Objective: We investigated the effects of conventional and hypofractionation protocols by modelling tumour control probability (TCP) and tumour recurrence time, and examined their impact on second cancer risks. The main objectives of this study include the following: (a) incorporate tumour recurrence time and second cancer risks into the TCP framework and analyse the effects of variable doses and (b) investigate an efficient protocol to reduce the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These conclusions would favor hypofractionated RT regimens in reducing SCR, as seen in our study. Manem et al showed in their work modeling tumor control probability and tumor recurrence time on the basis of the linear quadratic model and SCR on the basis of the IIP model [11] that with hypofractionation, SCR was reduced by 22 % compared to a conventional (2Gy) fractionation schedule [34]. Schneider et al also reported that SCR decreases linearly by around 10–15 % per 1 Gy for both carcinoma and sarcoma induction with increasing fractionation dose, and using conventional rather than stereotactic RT, where this effect has not been detected [35].…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions would favor hypofractionated RT regimens in reducing SCR, as seen in our study. Manem et al showed in their work modeling tumor control probability and tumor recurrence time on the basis of the linear quadratic model and SCR on the basis of the IIP model [11] that with hypofractionation, SCR was reduced by 22 % compared to a conventional (2Gy) fractionation schedule [34]. Schneider et al also reported that SCR decreases linearly by around 10–15 % per 1 Gy for both carcinoma and sarcoma induction with increasing fractionation dose, and using conventional rather than stereotactic RT, where this effect has not been detected [35].…”
Section: Discussionmentioning
confidence: 99%
“…Through our previous works, we characterized the biological imprecision of one-size-fits-all radiation dosing regimens by assessing patient-specific radiation-induced toxicities [ 6 , 8 ]. Furthermore, we curated a repertoire of published radiation response gene signatures [ 10 ], and reported that all the genomic signatures of radiation sensitivity were built using the NCI-60 dataset with limited to no independent external validation raising concerns about their reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we have witnessed a rapid evolution of technological advancements in radiotherapy treatment delivery and dose conformity through particle therapies, image-guided techniques [ 3 , 4 ] and the latest addition being the flash radiotherapy technique [ 5 ]. These significant advances have allowed the adaptation of radiation treatment planning fields based on anatomical changes of the gross tumor volume (in maximizing tumor control probability [ 6 ] and minimizing late toxicities either alone [ 7 , 8 ] or in combination with chemotherapy [ 9 ]). However, designing personalized radiotherapeutic regimens based on the tumor’s biological features is still hindered by the lack of appropriate clinical biomarkers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort and case control studies have indicated that there is an increased risk of second malignancies with young Hodgkin's Lymphoma survivors post irradiation (Bhatia and Sklar, 2002) (Hodgson et al, 2007b). Recently, several clinical and modeling studies have described the risk of of second malignancies for various neighboring organs (Sachs and Brenner, 2005) (Xu et al, 2008) (Moteabbed et al, 2014) (Paganetti et al, 2012) (Athar and Paganetti, 2011) (Hall, 2006) (Manem et al, 2014a). Some of these clinical studies have suggested that there is a high incidence rate of breast cancer among young Hodgkin's Lymphoma survivors compared to women treated in middle age (Travis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical findings indicate that second cancer risks change with respect to age at exposure and also with respect to time since exposure (Travis et al, 2005) (Dores et al, 2002). Some authors studied the efficacy of dose escalation on secondary cancer induction (Manem et al, 2014b) (Schneider et al, 2007). It has also been noted that the latency period is typically between 10 to 20 years for solid tumors, and around 5 years for leukemia post irradiation (Zhang et al, 2012) (Wang et al, 2014) (Schneider et al, 2014) (van Leeuwen et al, 2003) (Yeoh and Mikhaeel, 2010) (Yahalom, 2009) (Hodgson et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%